The Effectiveness of Problem-Based Learning Model with Ice Breaking on Self-Confidence at Primary School Students - Iis Nurasiah; Jembar Kitri Fauziah; Annisa Aulia Faiqoh; Zihan Nur Halizah; Muhammad Rifqi Fauzi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2026)
Objectives: This research aims to find the implementation of PBL with ice breaking and its effectiveness on self-confidence in speaking Rumi in sixth grade students at Nirandon Wittaya School in Thailand. Method: This research used a quasi-experimental approach with a one-group pre-test post-test design. The participants consisted of 30 students selected through purposive sampling. Data were collected using a standardized self-confidence questionnaire and a speaking performance observation rubric and analyzed using descriptive statistics and a paired t-test. Results: This research found five stages in implementing the PBL model with ice breaking: 1) ice breaking, 2) presentation of contextual problems, 3) working in groups, 4) presenting results, and 5) reflection. This research concluded that the Problem-Based Learning model with ice breaking was effective in improving the confidence of sixth-grade students in speaking Rumi at Nirandon Wittaya School, Thailand. Theoretical Contribution: The results of this research contribute to strengthening Bandura's Self-Efficacy Theory and the learning of al-tiqu bi al-nafs (self-confidence) and izzah (self-dignity) in Islamic education. Implication: This research has implications for the importance of problem-based learning and ice breaking to build student’s self-confidence in language learning.